The Role of Climate Change in the Spread of Infectious Diseases - Usmani, Asmatullah; Choopan , Abdul Kkhaliq (Journal of Natural Sciences – Kabul University, 2026)
Climate change not only contributes to drought, irregular precipitation, and floods, but also plays a significant role in the emergence and intensification of various infectious diseases. The primary driver of climate change is the emission of greenhouse gases, which leads to various climatic hazards. Consequently, wild animals, including reptiles, insects, and birds, which serve as reservoirs or vectors of infectious agents, are forced to migrate from their natural habitats toward urban areas, increasing their contact with human populations. This study is a literature-based review aimed at clarifying the relationship between climate change and infectious diseases. Our study highlights that rising temperatures, irregular rainfall patterns, drought, and deforestation are key factors that contribute to the increased incidence and severity of infectious diseases. Preventive measures against climate-related risks, strengthening public health surveillance, and conducting further research in this field are therefore essential.